Tirakat as Strengthening the Relationship between Parents and Children - Hasanah, Uswatun; Qibtiyah, Luthfatul; Khotijah, Sitti (Proceedings of International Conference on Muslim Society and Thought, 2024)
This research aims to examine tirakat in strengthening the relationship between parents and children. Tirakat is a spiritual practice in Javanese culture that involves self-control and prayer, in practice it becomes a medium for building a more harmonious relationship between parents and children. This research methodology uses a qualitative approach with interview and observation techniques. The research results show that the relationship between parents and children is a fundamental aspect in family and community life, this relationship aims to build a strong emotional attachment between the two, this emotional attachment remains strong even though physical distance separates parents and children, emotional was built well. one of the steps strengthen the emotional attachment between the two of them can be done by performing tirakat as follows; Reciting prayers (Sholawat), fasting, reciting verses from the Al-Qur’an, Shodaqoh and ablution water therapy. Recommendations for future research include exploring the impact of tirakat on various aspects of child development and the application of this practice in other communities